AI enabled mobile expense tracking for sole-proprietor businesses - Ong, Yew Han (Nanyang Technological University, 2023)
Accounting is a vital function for any business, as it helps to track the financial performance and position of the entity. However, accounting today has become ever complicated than before, due to the increasing complexity and diversity of business transactions and regulations. While large businesses use accounting software for their accounting, such systems are too complicated and expensive for small sole proprietorship businesses such as hawkers and freelancers, who often have limited resources and time to manage their finances. To tackle this problem, this project would focus on developing a modern mobile application that would assist small businesses in tracking their finances using Artificial Intelligence (AI) technology. The application would leverage the power of AI to automate and enhance various aspects of the expense tracking process such as expense tracking and data analysis. By doing so, the application would reduce human errors and increase accuracy and efficiency in accounting tasks.